Teacher Community in Urban Elementary Schools: The Role of Leadership and Bureaucratic Accountability - Weathers, John M. (Education Policy Analysis Archives, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Cambria; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif]--> <!--StartFragment--><span style="font-size: 12.0pt; mso-bidi-font-size: 10.0pt; font-family: Garamond; mso-fareast-font-family: Garamond; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US;">The purpose of this study is to determine the effect of principal leadership and accountability policies on teachers’ sense of community. This study is situated within the research and policy/practice discourse over the importance of schools developing a professional community of teachers who share common values, cooperate in support of these values, and a have sense of mutual accountability as a means of improving student achievement. However, to date, few studies have examined the effect of leadership practices and accountability policies on teacher communities, and these studies do not conceptualize and measure teacher community in line with theories of community. Additionally, there is a pervasive and mostly untested belief by advocates of teacher professionalization that top-down management, standards, and accountability policies are antithetical to teacher communities. Data for this study come from the National Center for Education Statistics’ (NCES) Schools and Staffing Survey (1999-2000). A two-level multilevel regression analysis was used with a public school urban elementary (K-5) subset of the SASS data. Principal leadership has a very strong positive effect on teacher community—the strongest effect of any policy-amenable variable. Significant principal actions include: recognizing teacher effort and communicating expectations; and a principal’s direct efforts to build community among teachers. The effect of teacher classroom control and policy influence is significant, but reduced by measures of principal leadership. Teachers’ use of standards is associated with a sense of community, but a somewhat limited measure of school performance-based accountability has no association. <!--EndFragment-->